REAKSI PASAR MODAL TERHADAP PERISTIWA VIRUS CORONA (COVID-19) PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sambuari, Inri B.; Saerang, Ivonne S.; Maramis, Joubert B. (FEB Universitas Sam Ratulangi Manado, 2020)
The capital market is not only a funding facility for the companies but also means for investment activities. So many roles of the capital market in economic activities will have an impact on the sensitivity of the market reaction to events that occur. At the end of 2019, a new virus emerged in China, called the Corona Virus Disease 2019 or COVID-19. In Indonesia, the first case of COVID-19 was approved directly by President Joko Widodo on March 2020. The purpose of this research is to discover informations regarding the first reporting of COVID-19 in Indonesia, as well as abnormal return, frequency of trade, and market capitalization before and after the event. The observation began 30 days before the event and 30 days after the event. This study uses quantitative research in the comparative method. The sample uses judgment sampling with total of 22 food and beverage companies listed on the Indonesia Stock Exchange. The finding show did not contain information that caused the market to be disapproved. This is proven by the absence of significant results in daily tests on the indicators. The results were also not significant in the combined abnormal return test and the combined market capitalization test. The trade comparison test results show a significant difference which means there was a market-panic towards trading activities after the event that caused some frequency differences, before and after the event in terms of trade transactions.Keywords: Event Study, Abnormal Return, Trading Frequency, Market Capitalization